Sex-specific Analysis of the Management and Outcome of Elderly Patients with Acute Myocardial Infarction - Siqi YANG, Hanxiong LIU, Xiuqiong YU, Lin TONG, Jin LI, Lianchao CHENG, Xu CHEN, Lingyao QI, Yan LUO, Lin CAI (Zhongguo quanke yixue, 2022)
Background There may be sex-specific differences in the treatment and outcome of elderly people with acute myocardial infarction (AMI) . However, few studies have reported sex-specific differences in management and prognosis of older Chinese people with AMI. Objective To assess the sex-specific differences in management strategies, in-hospital mortality and cardiovascular mortality within one year after discharge in older Chinese people with AMI. Methods We consecutively enrolled 1 579 elderly (>60 years of age) patients with AMI admitted to 11 tertiary general hospitals in Chengdu between January 2017 and June 2019, including 1 056 men and 523 women. Sex-specific analysis of clinical characteristics, management strategies and 1-year outcome were performed. Kaplan-Meier estimator was used to describe the incidences of cardiovascular death within one year after discharge between men and women and the associated factors were explored using multivariate Cox proportions hazards regression analysis. Results Female patients had lower prevalence of smoking, and alcohol consumption, history of percutaneous coronary intervention and chronic obstructive pulmonary disease, typical symptoms including chest pain and chest tightness, and use of dual antiplatelet agents and statins, and lower mean creatinine levels than male patients (P<0.05) . Moreover, female patients had older mean age, diabetes, and higher mean heart rate, greater prevalence of Killip class≥Ⅱ, and higher mean level of total cholesterol, longer mean symptom-onset-to-balloon time and first medical contact to balloon dilation time, and higher in-hospital mortality rate (P<0.05) . Furthermore, the cardiovascular mortality rate within one year after discharge was higher in women (P<0.05) . Multivariate Cox proportions hazards regression analysis showed sex〔HR=1.830, 95%CI (1.029, 3.255) , P=0.040〕, age〔HR=1.063, 95%CI (1.031, 1.095) , P<0.001〕, ST-segment elevation myocardial infarction〔HR=2.382, 95%CI (1.380, 4.113) , P=0.002〕, cardiogenic shock〔HR=2.474, 95%CI (1.259, 4.859) , P=0.009〕, creatinine〔HR=1.004, 95%CI (1.001, 1.006) , P=0.003〕 and PCI〔HR=0.228, 95%CI (0.135, 0.386) , P<0.001〕 were associated with cardiovascular death within one year after discharge. Conclusion The rates of reperfusion treatment in older women and men with AMI were similar, but there were differences in treatment efficiency and outcome. Older women with AMI had lower in-hospital treatment efficacy, longer total myocardial ischemia time, lower prevalence of pharmacological treatment, and higher in-hospital all-cause mortality and cardiovascular mortality within one year after discharge.